Mapping Mental Well-being in Cities: A Narrative Review of Urban Mental Health Determinants - Aryuni, Muthia; Holis, Ade; Marwah, Sopa Siti (Yayasan Sinergi Kawula Muda, 2023)
Urbanization has significantly reshaped social and environmental landscapes, posing complex challenges to mental health in densely populated areas. This narrative review aims to explore how urban stressors—both social and physical—influence psychological well-being, and what interventions may mitigate their impact. Literature was collected through comprehensive searches in PubMed, Scopus, and Google Scholar using keywords such as